Ground Penetrating Radar (GPR) Type KSD-24 Application For Utility Identification Under Road Pavement Surface - Hamdani, Dani; Yamin, Raden Anwar; Andani, Rikal; Dhanardono, Bhima (Politeknik Pekerjaan Umum, 2025)
The research background is to identification the position of utilities such as drinking water pipes, waste water pipes, fiber optic cables, and electrical cables below the road surface that have not been properly mapped when excavation work or road preservation. This study aims to utilize the KSD-24 type GPR that was just owned by PUtech in early 2024. The research method used is primary data collection from GPR brand Koden Electronics Co., Ltd with type KSD-24. Data collection was conducted on two paths that pass-through utilities. The data processed and interpreted in the form of radargram images. The results of the study indicate that the KSD-24 GPR tool can obtain information about the existence of utility networks below the road surface. The results of the radargram image from the KSD-24 GPR tool provide the same distance and depth display on utility installations/installations, both utilities without water volume/dry such as water pipes, steel reinforcement series and cable installations. Likewise for utilities with additional water volume as a simulation of under ground drainage. The KSD-24 type GPR tool is proposed to be included in the curriculum, specifically the Road and Bridge Inspection course in the Road and Bridge Construction Technology Study Program.